O PROFMAT como política de formação continuada de professores de Matemática : concepções educacionais e implicações pedagógicas - Duarte, Pollyana Cristina (2021)
The “Mestrado Profissional em Matemática em Rede Nacional (PROFMAT)” is a Stricto Sensu graduate program focused on mathematic content and aims to promote a continuous formation of teachers in order to improve basic education index. This program was stablished in Brazilian universities since 2011 as a precursor of other professional master's degrees in the Master’s Programs for Teacher Qualification in the Public Network of Basic Education (ProEB), which aim to provide the teacher with continuing education. This research is a critical analysis of PROFMAT aiming to point the program as a continuous formation policy in the approach of educational conception and pedagogic implication in this process. Thus, guiding documents were analyzed from the content analysis based on theoretical references considering the neoliberalism influence as Crhistian Laval, Stephen J. Ball, Eneida Oto Shiroma, Dario Fiorentini, Ana Lúcia Manrique, Susana Beatriz Szewcyk, among others. In this methodological design, the research of a qualitative nature is characterized, using the technical procedure of document analysis, investigating the guiding documents of the program. We identified that a posteriori category that served as a basis for analysis, namely: PROFMAT as an Educational Public Policy, objectives and guidelines, curriculum and pedagogical books, norms for course completion papers and national exams, being the National Access Examination (ENA) and the National Qualification Examination (ENQ). As a result, is possible to conclude that the program is derived from educational reforms and can be understood as a public policy that aims to train and qualify Mathematics teachers in continuous education. In its foundations, the program approaches a political strategy for the control of teachers, meeting a neoliberal logic of education, in precepts of a traditional and technicist education of teacher professionalization. The program is supported by a content teaching in the instrumental view, which values the field of pure Mathematics at the expense of Mathematics Education, and this causes dichotomies that impact the training and work of Mathematics teachers. Therefore, the program's objectives are disconnected from the objective needs of the school reality.